3D velocity measurement by a single camera using Doppler phase-shifting holography. (16th September 2016) - Ninomiya, Nao; Kubo, Yamato; Barada, Daisuke; Kiire, Tomohiro
Abstract: In order to understand the details of the flow field in micro- and nano-fluidic devices, it is necessary to measure the 3D velocities under a microscopy. Thus, there is a strong need for the development of a new measuring technique for 3D velocity by a single camera. One solution is the use of holography, but it is well known that the accuracy in the depth direction is very poor for the commonly used in-line holography. At present, the Doppler phase-shifting holography is used for the 3D measurement of an object. This method extracts the signal of a fixed frequency caused by the Doppler beat between the object light and the reference light. It can measure the 3D shape precisely. Here, the frequency of the Doppler beat is determined by the velocity difference between the object light and the reference light. This implies that the velocity of an object can be calculated by the Doppler frequency. In this study, a Japanese 5 yen coin was traversed at a constant speed and its holography has been observed by a high-speed camera. By extracting only the first order diffraction signal at the Doppler frequency, a precise measurement of the shape and the position of a 5 yen coin has been achieved. At the same time, the longitudinal velocity of a 5 yen coin can be measured by the Doppler frequency. Furthermore, the lateral velocities are obtained by particle image velocimetry (PIV) method. A 5 yen coin has been traversed at different angles and its shapes and the 3D velocities have been measured accurately. This method can be applied to the particle flows in the micro- or nano-devices, and the 3D velocities will be measured under microscopes.